Thinking About Political Education in Formal Education - Ana Corina Fernández Alatorre (Universidad Nacional, Costa Rica, 2018)
The purpose of this essay is to share the reflections about the meaning of politics to be able to think, from there, of the potential of a kind of education capable of giving back to the subject the right to take the floor and act, to exercise the politicization in the best possible way. From what is currently observed in countries of different continents, especially those with great inequalities, high levels of corruption and vulnerable sovereignty, the texts of Hannah Arendt (1997) are taken as a source of theoretical reflection in order to bring her into dialogue with more contemporary authors, like Bauman (2001), who invite us to recognize the many devastating faces of fear and their consequent paralyzing effect. After arguing the need to restore politics, reflection is opened to think about the implications of this need for the meaning of education.